Viscosities of mixtures of 2-alkanols with tetraethyleneglycol dimethyl ether at different temperatures - Aznarez, S. (2006)
Kinematic viscosities and densities were measured over the entire range of composition and at atmospheric pressure for 2-propanol-tetraethyleneglycol dimethyl ether, 2-butanol-tetraethylene glycol dimethyl ether, and 2-pentanol-tetraethylene glycol dimethyl ether from 288.15 to 318.15 K employing pure species and solutions covering the whole range expressed by the condition 0 ≤ x ≤ 1. Starting from the experimental data, the dynamic viscosity, deviation of dynamic viscosity, and the excess Gibbs energies of activation for viscous flow have been calculated. The results were fitted by the Redlich-Kister equation. Free-volume type correlation with one parameter is compared with an extension of the generalized corresponding states principle for these systems.